The Living Qur'an: Self-Healing dengan Ayat-ayat al-Qur'an - Ulviyatun Ni'mah (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2022)
Self-healing is currently becoming popular among the public. Slightly different from the definition that should be, the term self-healing is often used for activities that are an escape from boredom or stress. Of the many options, many people use the Qur'an for healing, either for physical or psychological ailments. The use of the Qur'an for self-healing and for others is a practical form of living the Qur'an. Living Qur'an is defined as an effort to ground the Qur'an. In the scientific discourse on the Qur'an, the living Qur'an is one of the approaches used to study the Qur'an. The focus of this paper is the use of the verses of the Qur'an in self-healing which is framed in the study of the Living Qur'an. In this study, the author uses a qualitative method (qualitative approach) which is done by collecting as much data as possible. The method used in compiling this paper is by using library research. The results of this paper, a number of verses of the Qur'an which reveal that the Qur'an is a medicine (shifa’) or an antidote to disease. In its development, many verses of the Qur'an are also used as medicine to cure or relieve disease.